Defining and Developing Measures of Checklist for Measuring Food Store Environment: A Systematic Review - Nahid ZERAFATI-SHOAE; Mohammad Hosseint TAGHDISI; Leila AZADBAKHT; Hamid SHARIF NIA; Naheed ARYAEIAN (Tehran University of Medical Sciences, 2021)
Background: Food store measurement is important for planners and policy makers to improve unhealthy stores towards healthy stores. This review aimed to outline the concepts and measures development of checklists that assess food store environment in urban communities. Methods: The search was carried out in PubMed, Embase, Web of Science and Scopus as well as reference lists of included studies for obtaining published articles between 1990 up to the date of search (30 June 2017). Eligibility criteria attempted to capture peer-reviewed articles aimed at development and validation of checklists for assessing food stores. Results: From 3,862 records, 24 studies were included in this review. Findings showed constructs included in the instruments were availability (n=22); price (n=22); quality of fresh foods (n=13); promotion (n=6); product placement (n=6); advertisement (n=5); shelf space (n=3); display (n=3); store features or characteristics (n=2); marketing (n=2); accessibility; nutrition information; visibility; food variety; signage. There are differences on the conceptual definition of each constructs across the checklists. Only half of studies pursued fully systematic steps for the measures development. Conclusion: Consensus for definition of constructs of food store measurement is necessary. Besides, the development of the measures of checklists needs to be done by high-quality methods.